Wake in fright - Cook, Kenneth 1929-1987; Scott, John 1930- (Eureka, 2014)
"Balanced on a knife-edge between social realism and existential horror, this disturbing, subversive portrayal of Australia's cultural underbelly failed to find a wide audience on its original release, but has since become stablished as a seminal cornerstone of the Australian cinema. A middle-class schoolteacher, stuck in a government-enforced teaching post in an arid backwater, stops off in the mining town of Bundanyabba on his way home for the Christmas holidays. Discovering a local gambling craze that may grant him the financial independence to move back to Sydney for good, the opportunity proves irresistible. But the bad decisions are just the beginning and a reliance on local standards of hospitality in "the Yabba" may take him on a path darker than ever expected." [bbfc.co.uk]
Bildformat 1.85:1
Orig.: USA, Australien 1971
Enth. feature length audio commentary with director Ted Kotcheff and editor Anthony Buckley ; video interview from 2009 with Ted Kotcheff ; ABC's 7:30 Report: video piece on the the rediscovery and restoration of the film ; "Who needs art?": vintage piece on "Wake in fright" ; Chips Rafferty obituary clip ; outback TV spot ; UK theatrical trailer ; 18-page booklet featuring essays by Adrian Martin, Peter Calvin, Meg Labrum, Graham shirley, Ted Kotcheff and Anthony Buckley, and archival imagery